The EFFECT OF EMPLOYEE ENGAGEMENT AND GREEN HUMAN RESOURCE MANAGEMENT (HRM) ON PERFORMANCE THROUGH EMPLOYEE COMPETENCE AT THE JEMBER REGENCY HEALTH OFFICE - Andri Desy Nurdiyanto; Budi Santoso; Ni Nyoman Putu Martini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of employee engagement and green human resource management on the performance of employees of the Jember Regency Health Office, with employee competence as an intervening variable. The research method uses a quantitative approach with data collection techniques through questionnaires distributed to Health Office employees. The data was analyzed using a path analysis technique to test the direct and indirect relationships between variables. The results of the study show that employee engagement and green human resource management have a positive and significant effect on employee performance directly. In addition, employee engagement and green human resource management also have a positive effect on employee competence. Employee competence has been proven to play a role as an intervening variable that strengthens the influence of employee engagement and green human resource management on performance. Thus, increasing work attachment and implementing environmentally friendly human resource policies can improve employee competence, which ultimately has a positive impact on the performance of Jember Regency Health Office employees. This study recommends that management further develop programs that increase work attachment and the implementation of green human resource management to support sustainable competency and employee performance improvement.